Phytogeography of pteridophytes on limestone areas in Guangdong, China - Wang, Fa-Guo; Wang, Ai-Hua; He, Rong-Rong; Yang, Dong-Mei; He, Chun-Mei; Liu, Dong-Ming; Moynihan, Jeremy; Yi, Qi-Fei; Xing, Fu-Wu (Phytotaxa, 2017)
Guangdong Province, located in southern China, is of great interest in studies of plant geography and conservation in limestone areas because of its rich biodiversity. We: (1) performed a phytogeographical analysis of pteridophytes in the limestone areas in Guangdong, (2) evaluated and determined levels of endemism, and (3) identified affinities with the floras of neighboring limestone areas. We found that some families show a preference for limestone habitats, e.g., Hypodematiaceae, Lygodiaceae, and Adiantaceae, are typical elements among pteridophytes in the limestone regions of Guangdong. In addition, some genera or section, such as Hypodematium, and Polystichum sect. Cyrtogonellum, show an exclusive preference for limestone habitats. The predominant phytogeographical affinities identified were East Asia, Chinese endemic, and Tropical Asia. We concluded that: (1) the limestone fern flora of Guangdong is principally subtropical in nature and represents southern subtropical flora at the margins of the northern tropics, with a strong interaction with the East Asian flora, (2) the limestone fern flora of Guangdong has a phytogeographical affinity with Japan, though the floras of neighboring Guangxi and Hainan Provinces have higher similarity with it.